Adenoid cystic carcinoma of the breast from a single-center cohort. (2015) - Kander, Elizabeth; Raza, Sania; Dhamne, Sagar; Solari, Mariana; Jain, Sarika
Abstract: Adenoid cystic carcinoma (ACC) of the breast is a rare breast tumor, comprising less than 1% of breast adenocarcinomas. Histopathologically, it is estrogen receptor (ER), progesterone receptor (PR), and HER2-negative (i.e., triple negative) but has a more indolent course than typical triple negative breast cancers. Most of what is known regarding ACC of the breast's treatment and prognosis is from case reports and case series. This case series reports a single institution's experience with ACC. Between 2003 and 2014, seven patients were found to have ACC of the breast. Most (6 of 7 cases) presented as a mammogram abnormality on routine screening. One patient was lost to follow up after initial diagnosis. All six patients underwent lumpectomy, sentinel lymph node biopsy (SLNB), and adjuvant radiation. None received systemic endocrine therapy or chemotherapy. All of the patients are without disease recurrence at median follow up of 6.2 years (range 0.4–10). Given the generally excellent prognosis of ACC of the breast and low tumor metastatic potential, it is reasonable to withhold adjuvant chemotherapy in the treatment of ACC and instead manage this malignancy with local therapy.